Lactylation-driven METTL3-mediated RNA m6A modification promotes immunosuppression of tumor-infiltrating myeloid cells - Xiong, Jia; He, Jia; Zhu, Jun; Pan, Jiongli; Liao, Weijie; Ye, Hongying; Wang, Haofei; Song, Yinjing; Du, Yue; Cui, Bijun; Xue, Maoguang; Zheng, Wanling; et al. (Molecular cell, 2022)
Tumor-infiltrating myeloid cells (TIMs) are crucial cell populations involved in tumor immune escape, and their functions are regulated by multiple epigenetic mechanisms. The precise regulation mode of RNA N6-methyladenosine (m6A) modification in controlling TIM function is still poorly understood. Our study revealed that the increased expression of methyltransferase-like 3 (METTL3) in TIMs was correlated with the poor prognosis of colon cancer patients, and myeloid deficiency of METTL3 attenuated tumor growth in mice. METTL3 mediated m6A modification on Jak1 mRNA in TIMs, the m6A-YTHDF1 axis enhanced JAK1 protein translation efficiency and subsequent phosphorylation of STAT3. Lactate accumulated in tumor microenvironment potently induced METTL3 upregulation in TIMs via H3K18 lactylation. Interestingly, we identified two lactylation modification sites in the zinc-finger domain of METTL3, which was essential for METTL3 to capture target RNA. Our results emphasize the importance of lactylation-driven METTL3-mediated RNA m6A modification for promoting the immunosuppressive capacity of TIMs.Tumor-infiltrating myeloid cells (TIMs) are crucial cell populations involved in tumor immune escape, and their functions are regulated by multiple epigenetic mechanisms. The precise regulation mode of RNA N6-methyladenosine (m6A) modification in controlling TIM function is still poorly understood. Our study revealed that the increased expression of methyltransferase-like 3 (METTL3) in TIMs was correlated with the poor prognosis of colon cancer patients, and myeloid deficiency of METTL3 attenuated tumor growth in mice. METTL3 mediated m6A modification on Jak1 mRNA in TIMs, the m6A-YTHDF1 axis enhanced JAK1 protein translation efficiency and subsequent phosphorylation of STAT3. Lactate accumulated in tumor microenvironment potently induced METTL3 upregulation in TIMs via H3K18 lactylation. Interestingly, we identified two lactylation modification sites in the zinc-finger domain of METTL3, which was essential for METTL3 to capture target RNA. Our results emphasize the importance of lactylation-driven METTL3-mediated RNA m6A modification for promoting the immunosuppressive capacity of TIMs.